On the multispacecraft determination of periodic surface wave phase speeds and wavelengths - Foullon, C. (2010)
Observations of surface waves on the magnetopause indicate a wide range of phase velocities and wavelengths. Their multispacecraft analysis allows a more precise determination of wave characteristics than ever before and reveal shortcomings of approximations to the phase speed that take a predetermined fraction of the magnetosheath speed or the average flow velocity in the boundary layer. We show that time lags between two or more spacecraft can give a qualitative upper estimate, and we confirm the unreliability of flow approximations often used by analyzing a few cases. Using two-point distant magnetic field observations and spectral analysis of the tailward magnetic field component, we propose an alternative method to estimate the wavelength and phase speed at a single spacecraft from a statistical fit to the data at the other site. Copyright 2010 by the American Geophysical Union.